Increased Light Intensity Mitigates CO2 and CH4 Emissions from Paddy Soil by Mediating Iron Redox Cycling Coupled with Organic Carbon Transformation - Lirong Sun; Mengxiao Jiang; Meng Li; Xugang Wang; Yafeng Han; Xianni Chen (Agronomy)
Iron redox cycling in paddy soils drives the release and mineralisation of dissolved organic carbon (DOC), influencing the emission of CO2 and CH4. Light irradiation exerts an inhibitory effect on the mineralisation of soil organic carbon, but the responses to light intensity of iron redox processes coupled with organic carbon transformation and greenhouse gas emissions remain underexplored. Here, we conducted a slurry incubation experiment with paddy soil at varying light intensities. The dynamics of soil ferrous iron [Fe(II)], DOC, dissolved inorganic carbon (DIC), and chlorophyll a, as well as headspace CO2 and CH4, were monitored over a 40-day period. The results demonstrated that light irradiation inhibited iron reduction, leading to a 58.1–74.7% decrease in soil Fe(II) concentration compared to dark incubation. The oxidation of Fe(II) generated from iron reduction was enhanced under light incubation (3.12–3.53 mg g−1), and the oxidation rate constant trended higher with increasing light intensity. Light irradiation reduced CO2 and CH4 emissions to 8.8–76.9% and 2.3–6.7% of those under dark incubation, respectively. With the extension of incubation time, soil DIC concentration showed an increase followed by a decrease under light incubation, and the earlier DIC decrease occurred at higher light intensities. The DOC decrease rate constant was greater under light incubation (0.024–0.042 d−1) than under dark incubation (0.012 d−1). Light irradiation activated phototrophic microorganisms producing chlorophyll a (4.71–6.46 mg g−1), whereas this pigment was undetectable under dark incubation. Organic carbon mineralisation was positively correlated with Fe(II) concentration, and Fe(II) oxidation was positively correlated with chlorophyll a concentration and DOC decrease (p < 0.05). Agricultural practices optimizing light exposure, such as shallow flooding or reducing plant density, are promising approaches to bolster DOC sequestration and mitigate CO2 and CH4 emissions in paddy fields.